Effects of high-energy ion-beam irradiation on structural and optical properties of (Mg0.95Co0.05)TiO3 thin films. Issue 1 (1st February 2018) - Santhosh Kumar, T.; Vinod, Arun; Rathore, Mahendra Singh; Pathak, A. P.; Singh, Fouran; Pamu, D.; Srinivasa Rao, N.
ABSTRACT: We report the structural and optical properties of high-energy ion-beam irradiated Co-doped magnesium titanate thin films. (Mg0.95 Co0.05 )TiO3 (MCT) thin films were deposited on quartz substrates using radio frequency magnetron sputtering. Subsequently, the films were annealed for crystallinity and were irradiated with 100 MeV Ag ions by varying the ion fluence. The X-ray diffraction patterns of the films before and after the irradiation were refined using the Rietveld refinement and the variations in the lattice parameters were correlated with the ion fluence. Although, annealing of thin films results in an enhancement in refractive index and optical bandgap, the ion fluence induces significant changes in the refractive index and optical bandgap. Atomic force microscopy is employed to study the surface morphology of the films. The impact of ion fluence on structural and optical properties of MCT thin films has been investigated.